# The expression x += y and x = x+y

- 2020-06-07 04:41:39
- OfStack

preface

This article mainly introduces the difference between x += y and x = x+y in Python. Share it for your reference and study. Here is a detailed introduction:

Look directly at the following code:

x +=y

```
In [66]: id(a)
Out[66]: 4476839480
In [67]: id(b)
Out[67]: 4476839480
In [68]: a = [1, 2, 3]
In [69]: b = a
In [70]: id(a)
Out[70]: 4477149984
In [71]: id(b)
Out[71]: 4477149984
In [72]: a += [4, 5, 6]
In [73]: a
Out[73]: [1, 2, 3, 4, 5, 6]
In [74]: b
Out[74]: [1, 2, 3, 4, 5, 6]
In [75]: id(a)
Out[75]: 4477149984
In [76]: id(b)
Out[76]: 4477149984
```

x = x + y

```
In [77]: a = [1, 2, 3]
In [78]: b = a
In [79]: id(a)
Out[79]: 4476686208
In [80]: id(b)
Out[80]: 4476686208
In [81]: a = a + [4, 5, 6]
In [82]: a
Out[82]: [1, 2, 3, 4, 5, 6]
In [83]: b
Out[83]: [1, 2, 3]
In [84]: id(a)
Out[84]: 4477187640
In [85]: id(b)
Out[85]: 4476686208
```

You can see that for mutable objects the form x = x + y has changed the point of x instead of "inplace".

dis module was used for 1 verification.

```
In [86]: def foo(x, y):
...: x += y
...: return x
...:
In [87]: def foo(x, y):
...: x += y
...:
In [88]: def foo2(x, y):
...: x = x + y
...:
In [89]: dis.dis(foo)
2 0 LOAD_FAST 0 (x)
3 LOAD_FAST 1 (y)
6 INPLACE_ADD
7 STORE_FAST 0 (x)
10 LOAD_CONST 0 (None)
13 RETURN_VALUE
In [90]: dis.dis(foo2)
2 0 LOAD_FAST 0 (x)
3 LOAD_FAST 1 (y)
6 BINARY_ADD
7 STORE_FAST 0 (x)
10 LOAD_CONST 0 (None)
13 RETURN_VALUE
```

You can see that the bytecode is different:

Corresponding INPLACE_ADD + = Corresponding BINARY_ADDNote: The above applies only to the CPython implementation.

conclusion